Caregivers’ Ability to Assess for Wasting Status of Their Under Five Children: A Cross Sectional Study at Mwanamugimu Nutrition Unit, Mulago National Referral Hospital, Kampala, Uganda - Prudence Ainomugisha; Hanifa Bachou; Martin Kasendwa; Amanda Murungi; Benard Owori; Susan Akriat; Richard Kajjura; Christopher Garamoi (Journal of Food Innovation, Nutrition, and Environmental Sciences)
Wasting, a form of malnutrition, continues to be a major childhood health challenge affecting over 50 million children annually. It remains more pronounced in the middle- and low-income countries and continues to pose a great threat to child survival; approximately 800,000 deaths due to wasting worldwide per year. Caregivers may play key roles in early identification and referral of wasted children for care. This study aimed to assess caregivers’ ability to measure wasting status of their children aged 6-59 months. A cross sectional study was conducted in September 2022; included caregivers of children 6-59 months while children with cerebral palsy, critical illness and bilateral oedema were excluded; 73 participants were enrolled, oriented on importance and use of Mid Upper Arm Circumference (MUAC), interviewed using pre-coded questionnaire and observational checklist. Reference MUAC measurements were conducted for respective children by a nutritionist. MS Excel 2018 and STATA 15 were used to analyze data. It was observed that caregivers could measure and categorize wasting status of their children using MUAC if supported. Overall, 72 (98.6%) of participants were able to measure MUAC and categorize the wasting status of their children with high sensitivity (100%, 97.5 Positive Predictive Value) and specificity (97.1% 100% Negative Predictive Value). High level of agreement was observed between participant’s and Nutritionist’s measurement and categorization of MUAC (k = 0.82).